Properties of fly ash based geopolymer for curing at ambient temperature - Nath, Pradip; Sarker, Prabir (Precast/Prestressed Concrete Institute, 2012)
Geopolymer concrete is a promising material with regard to precast construction for the ease of parametric and curing control. Most of the studies available in the literature used heat curing to demonstrate the properties of geopolymer mixture. This study aimed to achieve fly ash-based geopolymer suitable for ambient curing condition and eliminate energy consuming heat curing process. Class F fly ash was used as the base material which was reacted by sodium hydroxide and sodium silicate solutions. Ground granulated blast furnace slag (GGBFS) and calcium hydroxide (CH) was added in different proportions to the mixture. Setting times of geopolymer pastes and compressive strength after curing at 20-23°C were investigated. Results were compared with a control geopolymer mixture designed with fly ash alone as the binder. Inclusion of additives helped achieve setting time and compressive strength comparable to those of ordinary Portland cement (OPC). Setting time and compressive strength of geopolymers varied with the variation of alkaline activator to fly ash ratio. Generally, fly ash blended with slag or calcium hydroxide influenced the properties of geopolymer concrete cured at ambient temperature.